(untitled) (Journal of the Digital Humanities Association of Southern Africa, 2024)
South Africa is facing a literacy crisis, with the latest PIRLS results showing that 8 out of 10 learners cannot read for basic comprehension by the time they leave the foundation phase. In this climate, the development of strategies to assist educators in harnessing the available resources to maximum effect is needed. However, most teaching resources are not digitally available, and even fewer are available in formats that make them readily available for use in natural language applications.The Ngiyaqonda! project aims to provide an interactive, multimodal digital environment within which learners can practise their reading and writing skills. Computational grammars and speech technology are combined in a mobile application to facilitate the transition from oral competency in a language to written competency. In this paper, we show how words from a multilingual dictionary for foundation phase learners can be brought to digital life within the Ngiyaqonda! application to enhance the learning experience of core concepts and vocabulary.We use the official foundation phase CAPS English-isiZulu dictionary (Mbatha et al. 2018) to ensure that the content of the computational grammars is aligned with relevant learning outcomes. The result is a fully parallel, multilingual computational grammar that is aligned at the semantic level, ready to be included in the Ngiyaqonda! application.